Penyelesaian Harta Bersama di Pengadilan Agama Indonesia (Kasus di Pengadilan Agama Jakarta Selatan) - Rais, Isnawati (Universitas Islam Negeri Raden Intan Lampung, 2018)
The settlement of joint property, after husbands and wives divorced, is a crucial issue in the Religious Courts of Indonesia. According to the provisions of the Islamic Law Compilation (KHI) and Marriage Law No. 1/1974, a joint property should be divided equally if done peacefully. This research analyzes the joint property settlement after divorce in the Religious Court of South Jakarta and compares it with a number of cases in other similar institutions. This study finds out that the rules as stipulated both in the KHI and Marriage Law No. 1/1974, was not rigidly applied by the judges. Instead, the judges at the Religious Court of South Jakarta took a flexible and casuistic solution for the disputes over the sharing of joint property between divorced couples. The settlement methods used by the judges vary, depending on the case that occurs empirically. The peaceful settlement was also pursued by the Religious Court of South Jakarta, although in general, it was unsuccessful.